2021
DOI: 10.1007/s10584-021-03185-y
|View full text |Cite
|
Sign up to set email alerts
|

Threshold, budget and deadline: beyond the discourse of climate scarcity and control

Abstract: Since its inception, the Intergovernmental Panel on Climate Change (IPCC) has always been at the centre of the global climate debate. Its authoritative reports provide cultural resources for public understanding on the challenge of climate change. While the IPCC maintains its perception as a policy-neutral adviser, the IPCC in practice acts as a powerful discursive agent that guides policy debates in a certain direction by enacting influential scientific concepts. These concepts include three prominent metapho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…The second part involved fieldwork, as we performed participant observation over the two-week period of the 26th United Nations Climate Change Conference (COP26), and as part of a larger group of researchers interested in global climate governance (Aykut et al, 2022). Taking place in Glasgow, Scotland, COP26 represented a focal point for climate activists across the globe to rally around.…”
Section: Methods and Data Corpusmentioning
confidence: 99%
See 1 more Smart Citation
“…The second part involved fieldwork, as we performed participant observation over the two-week period of the 26th United Nations Climate Change Conference (COP26), and as part of a larger group of researchers interested in global climate governance (Aykut et al, 2022). Taking place in Glasgow, Scotland, COP26 represented a focal point for climate activists across the globe to rally around.…”
Section: Methods and Data Corpusmentioning
confidence: 99%
“…Embedded in the storeys that activists tell is information on where agency lies, which themes claim attention, and how interfaces between knowledge and policy are supposed to work. We thus employ a narrative analysis of a combination of online documents from XR in the United Kingdom with problem-centred interviews embedded in participant observation of the movement's direct action over the 2-week period of the 26th United Nations Climate Change Conference (COP26) and as part of a larger group of researchers interested in global climate governance (Aykut et al, 2022).…”
mentioning
confidence: 99%
“…A small change in economic activity or in environmental status, if crossing a threshold, may have enormous impacts (Farley 2012). Numerous studies have demonstrated existence of environmental or ecological thresholds, notably thresholds of biodiversity loss, ES degradation, and climate change, and many ESs (e.g., climate regulation and fish provision) are at critique state, hence small change in ESs' quantity may cause large changes in ESs' values (Asayama 2021;Farley 2012;IPBES 2019;IPCC 2018;Millennium Ecosystem Assessment 2005;Rockström et al 2009). ( 5) Even if marginal value is always diminishing, it is challenging and even infeasible to measure diminishment of marginal value in complex, highly interdependent economic systems and ecosystems (Ouyang et al 2020;Turner et al 1998).…”
Section: Overview Of the Concept Of Valuementioning
confidence: 99%
“…Although IPCC reports have never endorsed any specific temperature limit as a marker of 'dangerous' climate change, they have increasingly been framed around temperature increase as a unifying metric. This is seen, for example, in the so-called 'Reasons for Concern' framework, which was introduced in the Third Assessment Report (AR3) and lent credibility to the idea of considering climate impacts in relation to global temperature rise (Mahony, 2015;Asayama, 2021;see Chapter 21).…”
Section: Targets and Pathways: Dangerous Anthropogenic Objects?mentioning
confidence: 99%